Avoiding unnecessary radicalization in Bangladesh: learning from pakistan's counter-terrorism experiences in FATA - Clarke, Ryan (2016)
The recent incident involving the mutiny and possible infiltration of the Bangladesh Rifles by a terrorist group has raised concerns among security experts that Dhaka may be considering changing its current approach to dealing with terrorist groups by adopting a military-led strategy instead of maintaining its current policy of engagement through police and intelligence action. This brings front and centre the classical debate over police versus military action in combating terrorism. Before adopting such an approach it would be wise for the Bangladeshi government to examine Pakistan’s counter-terrorism experience in its Federally Administered Tribal Areas in order to avoid unnecessary radicalization in the country.